Effect of molybdate on crevice corrosion initiation of hydrogen-charged duplex stainless steel - Donghua Suo; Jinming Zhang; Wenbo Wu; Longlin Lei; Yangting Sun; Yiming Jiang; Jin Li (Journal of Materials Research and Technology, 2023)
In this paper, we studied the initiation of crevice corrosion of hydrogen-charged 2507 and investigated the effect of different Na2MoO4 concentrations on crevice corrosion. It was found that Na2MoO4 inhibits the adverse effect of hydrogen and enhances the inhibition of crevice corrosion. In addition, hydrogen-charged 2507 crevice corrosion initiates in the austenite phase. While Na2MoO4 improves the crevice corrosion resistance of both phases, crevice corrosion initiation sites changed in reverse, initiating in the ferrite phase.